2014
DOI: 10.1016/j.febslet.2014.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of insulin as a novel retinoic acid receptor‐related orphan receptor α target gene

Abstract: Edited by Laszlo Nagy Keywords:Retinoic acid receptor-related orphan receptor a Insulin Promoter Gene transcription a b s t r a c tInsulin plays an important role in regulation of lipid and glucose metabolism. Retinoic acid receptor-related orphan receptor a (RORa) modulates physiopathological processes such as dyslipidemia and diabetes. In this study, we found overexpression of RORa in INS1 cells resulted in increased expression and secretion of insulin. Suppression of endogenous RORa caused a decrease of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…They reported that the synthetic chemical SR1078 acts as a RORα/γ dual agonist, and stimulates the expression of two ROR target genes, G6Pase and FGF21 , in hepatocarcinoma cells (Wang et al, 2010). More recently, this chemical was reported to be useful as an anti-cancer therapeutic agent through a novel mechanism for the stabilization of p53 protein expression by RORα (Wang et al, 2012), and as an insulin-inducing agent through the activation of insulin transcription by RORα (Kuang et al, 2014). Thus, the identification of RORα/γ agonist would be of great value with regard to not only the augmentation of the innate immune system via Th17 cell activity, but also other beneficial physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the synthetic chemical SR1078 acts as a RORα/γ dual agonist, and stimulates the expression of two ROR target genes, G6Pase and FGF21 , in hepatocarcinoma cells (Wang et al, 2010). More recently, this chemical was reported to be useful as an anti-cancer therapeutic agent through a novel mechanism for the stabilization of p53 protein expression by RORα (Wang et al, 2012), and as an insulin-inducing agent through the activation of insulin transcription by RORα (Kuang et al, 2014). Thus, the identification of RORα/γ agonist would be of great value with regard to not only the augmentation of the innate immune system via Th17 cell activity, but also other beneficial physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The WST assay was used to detect cell viability as described previously. 17) In brief, RECs were incubated with 10 μL of reconstituted WST-1 mixture for 1 h at 37°C, and the values of absorption were measured at 440 nm (background at 630 nm was subtracted) by use of a synergy TM Multimode Microplate reader (Biotek, VT, USA). All experiments were performed in triplicates.…”
Section: Reagentsmentioning
confidence: 99%
“…Western blot was performed following the method we previously used. 17) RECs were lyzed with RIPA buffer at 4°C. The supernatant was collected, and the protein concentration was determined using a BCA protein assay kit (Shanghai Generay Biotech Co., Ltd).…”
Section: Mda and Sod Analysismentioning
confidence: 99%
“…RORA has been identified as controlling the transcription of genes important in the regulation of lipid and glucose metabolism, such as genes encoding apolipoproteins A1, A5 and C3, glucose 6-phosphatase, and insulin [6,7,8,9,10]. A spontaneous mutation consisting of a deletion within the RORA gene, that prevents translation of the RORA ligand-binding domain, has been identified in the staggerer mouse ( RORA sg/sg ) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to severe neurological disorders, RORA sg/sg mice are also characterized in modulating diet-induced obesity, insulin sensitivity and glucose uptake [12,13]. We recently found that the plasma insulin levels were regulated by locus-containing RORA on mouse chromosome 9 [14], and identified RORA as a transcriptional activator of insulin [10]. Moreover, RORA was identified as a T2DM susceptibility locus in Mexican Americans and Older Order Amish [15,16].…”
Section: Introductionmentioning
confidence: 99%